Ketone metabolism in the heart - Bin abdul kadir, A (2020)
The aphorism “fat burns in the flame of carbohydrate” leads to the question of whether the oxidation of the ketone body, D-β-hydroxybutyrate (βHB), is facilitated by anaplerosis via glycogen and/or glucogenic amino acids. The work in this thesis aimed to investigate the importance of anaplerosis in ketone body metabolism in the isolated heart. The first study (Chapter 3) determined whether glycolysis from glycogen affected the heart’s ability to oxidise βHB. The glycogen content of isolated rat hearts was altered by perfusion with or without glucose, before perfusing with Krebs-Henseleit (KH) buffer containing [14C]-βHB or [5-3H]-glucose to measure βHB oxidation and glycolytic rates, respectively. βHB oxidation in hearts with low glycogen (LG) was 2-fold lower than those with high glycogen (HG), and βHB oxidation rates directly correlated with glycogen content. βHB oxidation decreased glycolytic rates to ~0.2 μmol. gww-1.min-1 in all hearts, redirecting glucose into glycogen in LG heart, but not in HG hearts. βHB alone or with glucose increased the Krebs cycle intermediates, citrate, 2-oxoglutarate and succinate, and the total nicotinamide adenine dinucleotide phosphate (NADP/H) pool measured using metabolomics. Thus, glycogen is required for βHB oxidation. The second study (Chapter 4) determined the effect of βHB oxidation on cardiac energetics using 31P-NMR spectroscopy. In HG hearts, βHB oxidation increased the free energy of ATP hydrolysis (∆GATP) by increasing the concentration of phosphocreatine ([PCr]) and the phosphorylation potential, calculated from the [ATP]/[ADP][Pi] ratio. βHB oxidation was unable to increase the low ∆GATP in LG hearts due to low glycolytic flux through pyruvate. The third study (Chapter 5) defined the effect of the glucogenic amino acids, asparagine, valine and glutamine, on βHB oxidation in hearts with decreased flux through pyruvate to oxaloacetate (glycogen-depleted and perfused with low glucose buffer). Asparagine increased βHB oxidation 2-fold by increasing the metabolites of the malate-aspartate shuttle and purine nucleotide cycle, aspartate, fumarate and guanosine triphosphate. Neither valine nor glutamine increased βHB oxidation rates. The final study (Chapter 6) determined the effect of substrates and loading conditions on cardiac efficiency (the ratio between hydraulic work and oxygen consumption) in working rat hearts. Fatty acids were found to decrease cardiac efficiency, via increased oxygen consumption and decreased hydraulic work, at both low and high pre- and afterloads. At high, but not at low, pre- and after-loads, βHB plus acetoacetate (AcAc) increased efficiency by increasing hydraulic work. Thus, βHB plus AcAc increased cardiac efficiency more than glucose alone or with fatty acids at high pre- and after-loads. In conclusion, βHB oxidation and glycolysis from glycogen have a synergistic relationship in heart, which serves to increase the ∆GATP and thereby cardiac efficiency.